ECOLOGICAL DESIGN CONCEPT OF TEXTILE PRODUCTS: A STUDY ON BROCADE WEAVING MATERIALS OF THE CHINESE ETHNIC MINORITY YAO - YUAN, XING; CHUPRINA , N. (Art and Design, 2024)
Purpose of this study is to identify the principles of environmental feasibility that were applied in the design and reflected in the artistic style of textiles of the Chinese Yao ethnic minority; as well as in the formation of the means of their implementation in modern clothing design. Methodology. Through field research, the paper substantiates that the brocade textiles of the Chinese Yao ethnic minority embody ecological principles, such as the use of natural, degradable materials, resource conservation, and elimination of excess textiles. Also the work uses the methods of systematic generalization and classification, as well as the analysis of literary and scientific data to generalize the composition and diversity of artistic styles of traditional and modernized brocade textile patterns. Results. The ecological concept is an important principle followed by the Chinese Yao ethnic minority in the design and decoration of textiles. They apply its principles throughout the process of pattern making and brocade weaving, including cotton thread production, dyeing, embroidery, and garment design. Natural patterns such as octagonal floral and zoomorphic fish patterns were found to be preferred. A set of design cases from modern Chinese design brands and the textile company Hainan Lizhiyun Cultural Communication, which use the ecological concept in the development of fashionable clothing models for various purposes, was analyzed. It is characterized that traditional ethnic brocade textile elements and ecological principles are combined with modern creative design to bring new visual and design properties and achieve harmonious coexistence with the environment. Scientific novelty. The principles of environmental awareness in traditional and modern textile design of the Chinese Yao ethnic minority are identified. It is justified that it is based on the experience of adaptation to the natural environment and skillful application of ecological principles in the development and production of brocade textile products. It has been found that the ecological principles embedded in the traditional means of development of textile brocade products of the Yao ethnic minority have an inspiring influence on modern clothing design. It is emphasized that this is in line with the UN's advocacy of low-carbon and environmentally friendly production development, and therefore encourages the application of environmentally-oriented practices during the development of textiles and the design of textile products. Practical significance. As a result of the research, the main typical examples of textile patterns and colors of traditional Chinese ethnic Yao brocade, used in modern clothing design, were characterized. In addition, by combining the traditional ethnic patterns of Yao brocade with creativity, more creative design solutions can be created and cultural elements and connotations can be introduced into modern clothing design.